Digestibilidade aparente de hidrolisados proteicos de resíduos do abate de frangos e suínos pela tilápia do Nilo - Cardoso, Marjana dos Santos (2019)
The aim of this study was to determine the physicochemical composition of protein hydrolysates of meat by-products from poultry and swine processing, as well as to evaluate the apparent digestibility coefficients (CDA) of protein (CDAPB), energy (CDAEB) and essential amino acids. (CDAAAE) and nonessential (CDAAANE) by Nile tilapia juveniles. Analyzed the physicochemical composition (dry matter - MS; crude protein - PB; crude energy - EB; essential amino acids - AAE; non-essential amino acids - AANE) of swine liver protein hydrolysates (PHFS), swine mucosa (PHMS), feathers (PHP) and chicken (PHF). Five diets were formulated, one reference and four tests composed of 80% of the reference diet and 20% of hydrolyzed protein (PHFS, PHMS, PHP and PHF). For the apparent digestibility test 500 Nile tilapia juveniles (69.08 ± 0.69 grams) were randomly distributed in a water recirculation system composed of 20 cylindrical conical tanks (500L), adapted with feces collection cup. The animals were fed at a rate of 4% of live weight per day divided into five daily feeds, totaling 30 days of experimentation. It followed the indirect method of fecal collection using 0.1% Chromium III oxide (Cr2O3) as an inert marker. Significant differences were found between the CDAs of the different protein by-products hydrolysates of animal origin (P < 0.05) for practically all nutritional fractions analyzed, except for some amino acids such as arginine, tryptophan, cystine and taurine. The mean values of PHFS (87.53 and 79.53%), PHP (89.05 and 83.37%) and PHF (90.84 and 87.29%) for CDAPB and CDAEB respectively were lower (P > 0.05) the CDAPB (97.12%) and CDAEB (96.62%) means obtained for PHMS. In general, the CDAAAE averages; CDAAANE for PHMS (98.59%) were higher (P <0.05), however, it did not differ from PHP (95.45) and PHF (93.85), the lower averages were evidenced for PHFS (90.54%). The hydrolysates from poultry and swine slaughter byproducts showed high values of nutritional fractions of interest to aquaculture, in addition to high apparent digestibility rates for Nile tilapia. This study awakens to the use of hydrolysed proteins as functional food in animal nutrition.